Anthroponymy in Mohamed Nedali’s Writing: from Contact of Languages to Social Contrasts - Amrani, Oussama (Contrasts in humanities: literature, language, culture, 2023)
Mohamed Nedali is a contemporary Moroccan writer of French expression born in 1962 in Tahannaout, about thirty kilometers from Marrakech where he still lives. Having written eight novels with a realist vocation, he makes his region his favorite place and fiction because, as he says in an interview, “in literature one only speaks very well of a place one knows so well”. However, this attachment to space, or at least this rootedness in identity that demonstrate the territorial anchoring of the author, seems insufficient to serve his realistic vision. It is nevertheless true that the intrusion of vernacular languages in a text written in a foreign language is not without importance because it constitutes a significant element in a realistic fresco. Indeed, the text of Nedali is strewn with Moroccan expressions. This intrusion is not gratuitous and illustrates the role that the contact of languages can have in a fictional narrative. Moreover, the choice of anthroponyms in Nedali’s fiction is not arbitrary, as it is thoughtful and serves the author’s vision. Being a writer of soil and a good connoisseur of the Moroccan society, the author uses it to create a fresco whose contrasts illustrate his bias and his refusal of social evils.